Explaining the Australian marriage equality vote: An aggregate-level analysis. (May 2019) - Gravelle, Timothy B; Carson, Andrea
The Australian public voted in November 2017 in favour of changing the law to allow for same-sex marriage – only the second such national popular vote after Ireland in 2015. Though 61.6% of the Australian public voting in the Marriage Law Postal Survey voted Yes in support of marriage equality, this support was not uniformly distributed across the country, with support at the electoral division level varying between 26.1% and 83.7%. What, then, explains such variation in support for same-sex marriage among the Australian public? In this article, we advance an aggregate, electoral division-level explanation of the Yes vote that links support for the legalisation of same-sex marriage to a set of local-level political and socio-demographic factors.